Impact of changing gloves during cesarean section on postoperative infective complications: A systematic review and meta‐analysis. (13th May 2021) - Narice, Brenda F; Almeida, Joana R; Farrell, Tom; Madhuvrata, Priya
Abstract: Introduction: The cesarean section rate around the world, currently estimated at 21.1%, continues to increase. Women who undergo a cesarean section sustain a seven‐ to ten‐fold greater risk of infective morbidity compared with those who deliver vaginally. Material and methods: We aimed to assess the impact of changing gloves intraoperatively on post‐cesarean section infective morbidity (PROSPERO CRD42018110529). MEDLINE, Scopus, Web of Science, CINAHL, WHO Global Index Medicus, and Cochrane Central were searched for randomized controlled trials until June 2020. Published randomized controlled trials that evaluated the effects of glove changing during cesarean section on infective complications were considered eligible for the review. Two reviewers independently selected studies, assessed the risk of bias, and extracted data about interventions and adverse maternal outcomes. Dichotomous variables were presented and included in the meta‐analyses as risk ratios (RR) with 95% confidence intervals (CI). The quality of evidence was assessed using the GRADE approach in alignment with the recommendations from the Cochrane Review Group. Results: We identified seven randomized controlled trials reporting data over 1948 women. Changing gloves during a cesarean section was associated with a statistically significantly lower incidence of wound infective complications (RR 0.41, 95% CI 0.26–0.65, p  < 0.0001; GRADE moderate quality evidence). This intervention seemed to be effective only if performed after delivery of the placenta. No significant difference was seen in the incidence of endometritis (RR 0.96, 95% CI 0.78–1.20, p  = 0.74; GRADE moderate quality evidence) and/or febrile morbidity (RR 0.73, 95% CI 0.30–1.81, p  = 0.50; GRADE moderate quality evidence), regardless of the timing of the intervention. Conclusions: Changing gloves after delivery of the placenta during a cesarean section is associated with a significant reduction in the incidence of post‐surgical wound complications compared with keeping the same gloves throughout the whole surgery. However, an adequately powered study to assess the limitations and cost‐effectiveness of the intervention is needed before this recommendation can be translated into current clinical practice.